2013
DOI: 10.4081/ijas.2013.e79
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Different Selenium Levels on Production Performance and Biochemical Parameters of Broilers

Abstract: Selenium (Se) is an essential trace element for animal and human. Supplementation of Se usually in livestock diet has been proved as effective element. This study was conducted to investigate the effect of adding different levels of selenium yeast on growth performance, slaughter performance, immune trait, oxidation resistance, meat quality and selenium content in tissue of broilers to comprehensively evaluate the effect of selenium. A total of 540 day-old Arbor Acres (AA) broilers were selected and feeded wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 28 publications
10
26
1
Order By: Relevance
“…The results of the study indicate that the supplementation of Se did not influence body weight and feed efficiency. Similar findings have been reported by Chen et al (2013), who fed the chickens with different levels of selenium yeast. The results showed that effects of different levels of Se on growth performance, slaughter performance, the immune status, drip loss, and flesh did not significantly differ.…”
Section: Selenium and Poultry Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the study indicate that the supplementation of Se did not influence body weight and feed efficiency. Similar findings have been reported by Chen et al (2013), who fed the chickens with different levels of selenium yeast. The results showed that effects of different levels of Se on growth performance, slaughter performance, the immune status, drip loss, and flesh did not significantly differ.…”
Section: Selenium and Poultry Yieldsupporting
confidence: 90%
“…Effects of various sources and levels of Se in the diet on poultry yield have been subject of a number of studies Attia et al 2010;Heindl et al 2010;Yang et al 2012;Chen et al 2013;Habibian et al 2013;Rama Rao et al 2013 a.o.). The achieved results are not uniform, both negative and positive responses being reported.…”
Section: Selenium and Poultry Yieldmentioning
confidence: 99%
“…Similarly, Zhou and Wang, (2011), Yang et al (2012) and Senthil et al (2015) demonstrated that the Se supplementation presented the increased growth performance. But, on the other hand, Chen et al (2014) reported that non-significant result was observed regarding growth performance on Se added diet.…”
Section: Results Presented Inmentioning
confidence: 95%
“…While, Vogt (1994) found that choline supplementation improved growth. Likewise, some reports found no effect of different levels of Se or Se yeast on final LBW of the chickens (Habibian et al, 2013 andShourrap at el., 2018), LBWG, FI and FC , Yoon et al, 2007and Shourrap at el., 2018 and growth performance of broiler (Choct et al, 2004, Chen et al, 2013and Boostani et al, 2015 However, Yang et al (2012) show that Se yeast (0.3 mg/kg) could increase daily LBWG and FI by 8.92 and 3.99% and decrease FC by 4.84%, respectively. Also, Balti et al (2015) reported that average LBW at the end of the study, it was higher (P0.05) in the group with added 0.4 mg/kg Se as compared with no added Se and with the highest Se content in feed (0.6 mg/kg).…”
Section: Resultsmentioning
confidence: 99%